O DISCURSO TERAPÊUTICO E A CONSTRUÇÃO DA IDENTIDADE: UMA ANÁLISE DE DISCURSO CRÍTICA - Cortez, Marilene Tavares (Cadernos de Linguagem e Sociedade, 2010)
This paper examines approaches to therapeutic discourse from the point of view of Critical Discourse Analysis as it is conceived by Norman Fairclough. The main aim is to analyse how discourse practices affect the constitution of identities in late modernity. Two analytic models of therapeutic discourse will be critically revisited: the first one developed by Labov & Fanshel (1977) within the framework of Discourse Analysis, and the second developed by Ribeiro et alii (2002) within the framework of Interactional Sociolinguistics.